2D/2D Graphitic Carbon Nitride (g-C3N4) Heterojunction Nanocomposites for Photocatalysis: Why Does Face-to-Face Interface Matter? - Ong, Wee-Jun (Frontiers in Materials, 2017)
In recent years, two-dimensional (2D) graphitic carbon nitride (g-C3N4) has elicited interdisciplinary research fascination among the scientific communities due to its attractive properties such as appropriate band structures, visible-light absorption, and high chemical and thermal stability. At present, research aiming at engineering 2D g-C3N4 photocatalysts at an atomic and molecular level in conquering the global energy demand and environmental pollution has been thriving. In this review, the cutting-edge research progress on the 2D/2D g-C3N4-based hybrid nanoarchitectures will be systematically highlighted with a specific emphasis on a multitude of photocatalytic applications, not only in waste degradation for pollution alleviation, but also in renewable energy production (e.g. water splitting and carbon dioxide (CO2) reduction). By reviewing the substantial developments on this hot research platform, it is envisioned that the review will shed light and pave a new prospect for constructing high photocatalytic performance of 2D/2D g-C3N4-based system, which could also be extended to other related energy fields, namely solar cells, supercapacitors and electrocatalysis.